2017
DOI: 10.1039/c7lc00163k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound neuro-modulation chip: activation of sensory neurons in Caenorhabditis elegans by surface acoustic waves

Abstract: Ultrasound neuro-modulation has gained increasing attention as a non-invasive method. In this paper, we present an ultrasound neuro-modulation chip, capable of initiating reversal behaviour and activating neurons of C. elegans under the stimulation of a single-shot, short-pulsed ultrasound. About 85.29% ± 6.17% of worms respond to the ultrasound stimulation exhibiting reversal behaviour. Furthermore, the worms can adapt to the ultrasound stimulation with a lower acoustic pulse duration of stimulation. In vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 50 publications
2
60
0
Order By: Relevance
“…Recent studies have proven that ultrasound is capable of eliciting the action potentials and triggering various movement responses, including eye movement and limb movement . Our previous work demonstrated that C. elegans, a classical neural organism, responded to the ultrasound stimulation which could directly evoke the polymodal ASH sensory neurons . We also reported that ultrasound could efficiently stimulate the motor cortex in mice inducing the tail movement .…”
Section: Introductionmentioning
confidence: 93%
“…Recent studies have proven that ultrasound is capable of eliciting the action potentials and triggering various movement responses, including eye movement and limb movement . Our previous work demonstrated that C. elegans, a classical neural organism, responded to the ultrasound stimulation which could directly evoke the polymodal ASH sensory neurons . We also reported that ultrasound could efficiently stimulate the motor cortex in mice inducing the tail movement .…”
Section: Introductionmentioning
confidence: 93%
“…Both methods are actively being used in contemporary acoustofluidics as is evident from the following examples published in the literature the past two years. BAW devices have been used for cell focusing in simple and inexpensive aluminum devices [20], for binary particle separation in droplet microfluidics [21], for hematocrit determination [22], for enrichment of tumor cells from blood [23], and for manipulation of C. elegans [24,25], while SAW devices have been used for nanoparticle separation [26,27], for self-aligned particle focusing and patterning [28], for enhanced cell sorting [29], and for in-droplet microparticle separation [30]. Currently, the acoustofluidic devices with the highest throughput are of the BAW type [5].…”
Section: Introductionmentioning
confidence: 99%
“…Pilot studies have investigated the neural effects of ultrasound parameters, such as ultrasound fundamental frequencies (UFF), intensities (UI), durations (UD), duty cycles (UDC), pulse repetition frequencies (UPRF), etc. Besides a few human studies (Hameroff et al, 2013;Lee et al, 2016b;Legon et al, 2014), animal models, such as worms (Ibsen et al, 2015;Kubanek et al, 2018;Zhou et al, 2017), rodents (Tufail et al, 2010;Ye et al, 2016;Yu et al, 2016), rabbits , swine (Dallapiazza et al, 2018), and monkeys Folloni et al, 2019), have been utilized to investigate the effects of ultrasonic parameters and acoustic-induced effects. tFUS have been observed to induce behavioral changes, e.g.…”
Section: Introductionmentioning
confidence: 99%